PENGEMBANGAN BAHAN AJAR MAJALAH BERBASIS ANDROID PADA MATERI ADIKSIMBA BAHASA INDONESIA KELAS 4 SDN PURUT KOTA SERANG - Anna Qurrotul Ain; Sulastri, Dewi; Aprilia, Lusi; Jamaludin, Ujang; Setiawan, Sigit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The purpose of this study was to increase students’ literacy interest and students’ reading comprehension through the development of android magazine teaching materials on the ADIKSIMBA material for grade 4 Indonesian. The research method used was R&D with the borg and gall model. Analysis of research data using the Likert and Guttman scales. The research subjects were taken from 4th grade students at SDN Purut City of Serang. The results of the validation percentage recapitulation research by getting a value of 84.5% means that this teaching material is categorized as a very good teaching material and is very feasible to be tested on students and the initial test obtained an average score of 57.5 and in the final test obtained an average score 83 concluded that the use of teaching materials for this magazine can improve students’ understanding of interrogative sentences using the ADIKSIMBA element. ABSTRAK Tujuan pada penelitian ini adalah meningkatkan minat berliterasi siswa dan pemahaman membaca siswa melalui pengembangan bahan ajar majalah android pada materi ADIKSIMBA mata pelajaran Bahasa Indonesia kelas 4. Metode penelitian yang digunakan adalah R&D dengan jenis model borg and gall. Analisis data penelitian menggunakan skala likert dan guttman. Subjek penelitian diambil dari siswa kelas 4 SDN Purut Kota Serang. Hasil penelitian rekapitulasi persentasi validasi dengan mendapatkan nilai 84,5% artinya bahan ajar ini dikategorikan sebagai bahan ajar yang sangat baik dan sangat layak untuk diujicobakan kepada siswa dan tes awal didapatkan rata-rata nilai 57,5 dan pada tes akhir didapatkan rata-rata nilai 83 disimpulkan bahwa penggunaan bahan ajar majalah ini dapat meningkatkan pemahaman siswa tentang kalimat tanya menggunakan unsur ADIKSIMBA.